Utilization of Spirulina (Arthrospira Plantesis) in the Substitution of Taro Flour and Mocaf Flour in Dry Noodles as an Anti-Stunting Food Innovation - Adhisty Elcahyani; Siswi Astuti (Universitas Islam Raden Rahmat, Malang, 2025)
Stunting is a chronic nutritional problem that affects children's physical and cognitive development. This research aims to develop dry noodles made from taro flour, mocaf and spirulina as an alternative nutritious food for the prevention of stunting. Variations in the composition of taro flour and mocaf (60%:40%) with the addition of spirulina (2%) produced the best product with a protein content of 10.72%, carbohydrate content of 74.91% and moisture content of 6% according to SNI standards for dry noodles. Organoleptic tests showed that the sample was the most preferred by the panelists based on taste, texture, aroma, colour and crispness. Spirulina fortification contributed significantly to increasing the protein content and giving the product its characteristic green colour. This innovation is expected to help meet the nutritional needs of stunted children, support local food sustainability and reduce dependence on imported ingredients